User Experience Analysis of Mobile Banking Applications in Indonesia Using Usability Testing and the User Experience Questionnaire (UEQ): A Case Study of Bank Syariah Indonesia - Cherina Pancha Resyita; Najma Nur Maulida; Sucik Lestari (Journal of Islamic Studies and Education, 2024)
This study aims to explore user experiences in utilizing mobile banking applications in Indonesia through usability testing and the User Experience Questionnaire (UEQ). The rapid growth of mobile banking technology necessitates a focused approach to understanding user experiences to ensure applications are both efficient and satisfying to use. Usability testing is employed to evaluate how well mobile banking applications meet user needs and expectations. Users perform a series of tasks designed to cover the core features of the application, while researchers observe and record responses, difficulties, and the time required to complete each task. The results of the usability testing provide detailed insights into specific issues encountered by users when interacting with mobile banking applications. These findings offer an in-depth perspective on the strengths and weaknesses of existing mobile banking applications in Indonesia. This information can guide application developers in implementing necessary improvements and enhancements, ensuring that users have a more satisfying and efficient experience when using mobile banking services. Furthermore, this study contributes to raising awareness and understanding of user-centered development practices in mobile banking application design in Indonesia.